2016
DOI: 10.1097/md.0000000000002450
|View full text |Cite
|
Sign up to set email alerts
|

Appraising MicroRNA-155 as a Noninvasive Diagnostic Biomarker for Cancer Detection

Abstract: Cancer has been a major public health issue all over the world and cancer patients diagnosed at early stages have a comparatively favorable prognosis. The association between specific dysregulated expressed microRNA-155 (miRNA-155, miR-155) and tumorigenesis has been identified by numerous studies. However, perplexity and inconsistence arise from a wide range of studies due to heterogeneity. Therefore, this meta-analysis was carried out to validate the association between miR-155 and tumorigenesis together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 58 publications
0
23
0
2
Order By: Relevance
“…In accordance with these previous studies, we showed higher circulating miR-155 expression in breast cancer patients compared to healthy women. A meta-analysis involving 25 studies with total number of 1,896 breast cancer patients and 1,226 healthy controls showed the diagnostic accuracy of circulating miR-155 (Hou et al, 2016). Higher level of plasma miR-155 in early stage breast cancer has also been reported rendering its potential as early detection marker (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these previous studies, we showed higher circulating miR-155 expression in breast cancer patients compared to healthy women. A meta-analysis involving 25 studies with total number of 1,896 breast cancer patients and 1,226 healthy controls showed the diagnostic accuracy of circulating miR-155 (Hou et al, 2016). Higher level of plasma miR-155 in early stage breast cancer has also been reported rendering its potential as early detection marker (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have focused on the diagnostic value of dysregulated miRNAs in BC (12,53). however, this is the first identification of a nine-miRNA signature as a potential multi-marker for diagnosing BC found by analyzing high-throughput miRNA expression profiles from TCGA data.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of expression of plasma miRNAs have proven to be reliable as a prognostic indicator for some malignancies and infectious diseases (14,15). The current study has examined the potential of an miRNA expression profile in the plasma to serve as a biomarker in patients with active pulmonary TB and to predict the response to therapy.…”
Section: Introductionmentioning
confidence: 99%